BRCA1 heterozygosity promotes DNA damage-induced senescence in a sex-specific manner following repeated mild traumatic brain injury - Leung, Emily; Taskina, Daria; Schwab, Nicole; Hazrati, Lili-Naz (Frontiers in Neuroscience, 2023)
Emerging evidence suggests cellular senescence, as a consequence of excess DNA damage and deficient repair, to be a driver of brain dysfunction following repeated mild traumatic brain injury (rmTBI). This study aimed to further investigate the role of deficient DNA repair, specifically BRCA1-related repair, on DNA damage-induced senescence. BRCA1, a repair protein involved in maintaining genomic integrity with multiple roles in the central nervous system, was previously reported to be significantly downregulated in post-mortem brains with a history of rmTBI. Here we examined the effects of impaired BRCA1-related repair on DNA damage-induced senescence and outcomes 1-week post-rmTBI using mice with a heterozygous knockout for BRCA1 in a sex-segregated manner. Altered BRCA1 repair with rmTBI resulted in altered anxiety-related behaviours in males and females using elevated zero maze and contextual fear conditioning. Evaluating molecular markers associated with DNA damage signalling and senescence-related pathways revealed sex-specific differences attributed to BRCA1, where females exhibited elevated DNA damage, impaired DNA damage signalling, and dampened senescence onset compared to males. Overall, the results from this study highlight sex-specific consequences of aberrant DNA repair on outcomes post-injury, and further support a need to develop sex-specific treatments following rmTBI.